언어치료 전공학생의 대학생활 적응과 진로준비행동, 학습동기가 전공만족도에 미치는 영향 - 박현(Hyun Park); 한대성(Dae Sung Han) (언어치료연구, 2022)
목적: 이 연구는 언어치료 전공 대학생을 대상으로 대학생활적응, 학습동기, 진로준비행동에 대하여 알아보고 각 변수 간의 상관성을 알아보고자 실시하였다. 여러 요인의 관계와 더불어 각 요인이 전공만족도에 미치는 영향을 알아봄으로써 언어치료 전공학생들의 전공만족도를 높이는 방안을 알아보는 데 도움이 되고자 연구를 시행하였다. 방법: 연구는 언어치료학과에 재학 중인 학생 169명을 대상으로 대학생활적응(8문항), 학습동기(8문항), 진로준비행동(8문항), 전공만족도(5문항)를 조사하였다. 각 요인별 수준, 각 변수 간의 상관관계를 알아보았으며, 전공만족도에 영향을 미치는 요인을 알아보기 위하여 회귀분석을 실시하였다. 결과: 대학생활적응 수준에서는 수업 참여 여부가 가장 높은 항목(4.136)으로 조사되었으며, 학습동기 수준에서는 전공관련 학습 중요도(4.059)가 가장 높았다. 진로준비행동 수준에서는 주변사람들과 진로에 대하여 이야기하는 것(4.017)이 가장 높은 점수를 보였다. 모든 변수에서 상관관계가 높은 것으로 나타났으며, 전공만족도와의 상관관계는 대학생활적응, 학습동기, 진로준비행동 순으로 상관관계가 높게 나타났다. 전공만족도에 영향을 미치는 정도를 분석한 결과, 유용한 결과로써 대학생활적응, 학습동기, 진로준비행동 순으로 영향이 있는 것으로 조사되었다. 결론: 본 연구의 결과 언어치료학과 학생들은 대학생활적응, 학습동기, 진로준비행동이 전공만족도와 상관성이 높고 영향을 미치는 요인임을 알 수 있었다. 본 연구를 토대로 신입생의 대학생활적응을 돕고 재학 중 학습동기를 높이고 졸업을 준비하는 과정에서 진로준비행동을 도움으로써 언어치료 전공에 대한 만족도를 높이는 데 도움이 될 것이다. Purpose: This study was conducted to determine university life adaptation, learning motivation, and career preparation behavior for college students majoring in speech-language therapy and to measure the correlation between each variable. Methods: The study investigated 169 students. Data were collected through surveys with 29 questions, which included those about university life adaptation (8 questions), learning motivation (8 questions), career preparation behavior (8 questions), and major satisfaction (5 questions). The level of each factor and the correlation between each variable were examined and a regression analysis was conducted to determine the factors affecting major satisfaction. Results: At the level of university life adaptation, participation in classes was the highest (4.136), while at the level of learning motivation, major-related learning importance was the highest (4.059). In terms of career preparation behavior level, talking about career paths with people around them showed the highest score (4.017). The correlation with major satisfaction was in the order of university life adaptation, learning motivation, and career preparation behavior. Conclusions: As a result of this study, it was found that speech-language therapy students had a high correlation with major satisfaction and influence on university life adaptation, learning motivation, and career preparation behavior. Based on this study, it will help to improve satisfaction with the speech-language therapy major by helping new students adapt to college life, increasing motivation for learning while in school, and helping career preparation behavior in preparing for graduation. KCI Citation Count: 3